Global patterns and inferences of tuna movements and trophodynamics from stable isotope analysis. (May 2020) - Logan, J.M.; Pethybridge, H.; Lorrain, A.; Somes, C.J.; Allain, V.; Bodin, N.; Choy, C.A.; Duffy, L.; Goñi, N.; Graham, B.; Langlais, C.; Ménard, F.; et al.
Abstract: A global dataset of carbon stable isotope (δ 13 C) values from yellowfin, bigeye, and albacore tuna muscle tissue (n = 4275) was used to develop a novel tool to infer broad-scale movement and residency patterns of these highly mobile marine predators. This tool was coupled with environmental models and lipid content (C:N ratio) of tuna muscle tissues to examine ocean warming impacts on tuna ecology and bioenergetic condition across Longhurst provinces. Over a 16-year study period (2000–2015), latitudinal gradients in tuna δ 13 C values were consistent, with values decreasing with increasing latitude. Tuna δ 13 C values, reflecting modelled global phytoplankton δ 13 C landscapes ("isoscapes"), were largely related to spatial changes in oxygen concentrations at depth and temporal changes in sea surface temperature. Observed tuna isoscapes (δ 13 CLScorr ), corrected for lipid content and the Suess effect (oceanic changes in CO2 over time), were subtracted from model-predicted baseline isoscapes ( Δ 13 Ctuna-phyto ) to infer spatial movement and residency patterns of the different tuna species. Stable isotope niche width was calculated for each Longhurst province using Δ 13 Ctuna-phyto and baseline-corrected nitrogen isotope (δ 15 Ntuna-phyto ) values to further quantify isotopic variability as evidence of movements across isoscapes. A high degree of movement—defined as the deviation from the expected range of Δ 13 Ctuna-phyto values— was evident in three Longhurst provinces: Guinea current coast, Pacific equatorial divergence, and the North Pacific equatorial counter current. The highest level of population dispersal (variability in Δ 13 Ctuna-phyto values) was observed in Longhurst provinces within the western and central Pacific Oceans and in the Guinea current coast. While lipid content was low in yellowfin and bigeye, high and variable lipid stores in albacore muscle were consistent with seasonal movements between productive foraging and oligotrophic spawning habitats. Our ability to characterize tuna movement patterns without ambiguity remains challenged by uncertainty in trophic discrimination factors and ecological (e.g. diet variability) processes. However, this study illustrates that model-corrected δ 13 C values are a valuable, relatively cost-effective tool for identifying potential areas of mixing across management zones, particularly when electronic tagging studies are limited or absent. Stable isotope analyses of tuna tissues can therefore be an additional tool for guiding spatial stock assessments on top predator movement, dispersal patterns, and how they may be altered under a changing climate.